SP0087 Natural Occurring Lubricants To Maintain Joint Homeostasis. (15th July 2016) - Klein, J.
Abstract : Cartilage surfaces sliding past each other in the major joints (such as hips and knees) exhibit extremely low levels of friction under physiologically-high pressures, a lubricity which is essential for their healthy perfomance. A detailed molecular-level understanding of this could benefit treatments of osteoarthritis (OA), as well as improved prosthetic joint implants. Any insight must, first and foremost, be able to account for the low friction (coefficient of friction (CoF) down to ca. 0.001) at the high pressures (which can reach 100 atm or higher) of the joints. However, the main molecular "suspects" thought to constitute the lubricating boundary layer on cartilage, namely hyaluronic acid, lubricin or phospholipids, do not, individually, provide especially good lubrication. Recently 1 we discovered that hyaluronan (HA) which is attached to a surface – to resemble its configuration at the outer cartilage surface – may complex with phosphatidylcholines (PCs), lipids that are ubiquitous in synovial joints, to form robust boundary layers. These layers act synergistically to provide the very low friction (CoF $≈ $ 0.001) characteristic of cartilage, at the highest physiological pressures, and contrast with surface-attached HA on its own, which leads to considerably higher friction. The very low friction is ultimately due to the phosphocholine groups exposed by the HA/PC surface complexes; these groups are known to be strongly and highly-hydrated, and they lubricate via the recently elucidated hydration-lubrication mechanism 2 . Our results thus point to a scenario 3 where HA, PCs and lubricin, each with a very different role, act together synergistically to reduce friction of cartilage in articulating joints. Hyaluronan, anchored at the outer surface of articular cartilage by lubricin molecules (which are known to be present in the outer superficial zone), complexes with joint phosphatidylcholines to provide the extreme boundary lubrication of synovial joints via the hydration-lubrication mechanism. 1. Seror, J., Zhu, L., Goldberg, R., Day, A.J. and Klein J. Supramolecular synergy in the boundary lubrication of synovial joints. Nature Communications, | 6:6497 | DOI: 10.1038/ncomms7497 (2015) 2. Ma, L., Gaisinskaya, A., Kampf, N. and Klein, J. Origins of hydration lubrication. Nature Communications, | 6:6060 | DOI: 10.1038/ncomms7060 (2015) 3. Jahn S, Seror J, Klein J., Lubrication of articular cartilage. Annu. Rev. Biomed. Eng . 18:in press. DOI: 10.1146/annurev-bioeng-081514–123305 (2016) Disclosure of Interest: None declared